Development and implementation of an electronic health record system for use in humanitarian emergencies, disaster response, and conflict zones. - Sarah D Draugelis; Erik C Brown; Donald A Donahue; Justin Hickman; Sean G Smith; Philip Sutherland; George A Yendewa; Amir M Mohareb (PLOS Global Public Health)
Humanitarian medical response to natural and human-made disasters can be complicated by high clinician, staff, and patient turnover. While electronic medical records are being scaled up globally, their use remains limited in humanitarian response settings. The Fast Electronic Medical Record (fEMR) system is an open-source electronic health record system specifically designed for use in resource-limited settings and humanitarian crises. The system was developed between 2010-2014 through an iterative design process with multidisciplinary team members. It was operationalized in settings with and without internet connectivity. We analyzed data on fEMR usage since inception until October 2022 to estimate the number of patients served by the system. In eight years of implementation (2014-2022), the fEMR system has been deployed 60 times to 11 different countries across four different continents by 14 different organizations. These deployments collectively account for over 37,500 patient encounters with an estimated 31,940 distinct patients. The settings of fEMR use ranged from refugee and migrant health clinics near the Mexico-US border to the Poland-Ukraine border in the context of the 2022 war in Ukraine. User feedback demonstrated the program's ease of use by providers of different clinical and technical backgrounds. Feedback primarily emphasized improving the system's hardware requirements and workflow. The simple design allowed for clinician users to adapt the system to a variety of clinical scenarios. Ongoing and future work in adapting electronic health records to international humanitarian response will emphasize data security, patient privacy, equity, and the rapid translation of electronic health data to improve population health. In humanitarian response settings, electronic health records can improve quality of care and provide a source of clinical and management data for public health planning.